Evaluating Geostationary Lightning Mapper Flash Rates Within Intense Convective Storms. Issue 14 (17th July 2020) - Rutledge, S. A.; Hilburn, K. A.; Clayton, A.; Fuchs, B.; Miller, S. D.
Abstract: The Geostationary Lightning Mapper (GLM) marks the first time that lightning observations at storm‐scale resolution are operationally available from geostationary orbit. We evaluate GLM detection efficiency (DE) for a special class of convective storms characterized by anomalous charge structures. These storms are anomalous as their internal layered charge structure departs from the tripole charge structure model, where midlevel negative charge is situated between upper and lower positive charge layers. Anomalous storms are characterized by extreme flash rates, low median flash heights, and intense precipitation. Ground truth information on lightning flash rates is provided by Lightning Mapping Arrays (LMA), which measure VHF radio frequency emissions produced by electrical breakdown. This study contrasts two regions: Colorado, where electrically "anomalous" storms are numerous, and Alabama, where they are rare. This study analyzes GLM DE as a function of the precipitation water path, cloud water path, and lightning properties from LMA. The GLM DE is found to vary with the geometric size of the flash and with cloud water path, the latter depending on flash height and cloud water content. Optical scattering (attenuation) by precipitation‐sized particles does not appear to be a factor since precipitation particles contain much less surface area than cloud particles. The size of the flash is correlated with its optical brightness, and the cloud water path is correlated with optical extinction. Regional differences in GLM DE remain that appear to be related to sensor viewing geometry and day versus night sensitivity differences. Key Points: Geostationary Lightning Mapper (GLM) detection efficiency (DE) is characterized using Lightning Mapping Arrays Reduced detection efficiency (DE) is found for storms with anomalous charge structures Additional factors related to viewing geometry and day‐night effects are likely required to explain regional differences in DE